Negotiations of language ideology on the Jodel app: Language policy in everyday online interaction. (March 2020) - Heuman, Anna
Highlights: The commonsensicality of the standard enables implicit argumentation in metalinguistic debates. Mastering certain features of standard language are crucial for acceptance on the Jodel app. Linguistic norms are continuously negotiated and perpetuated in interaction. Abstract: This study explores language policy in micro interaction on the online discussion app Jodel. By analyzing metalinguistic, evaluative comments, this study aims to provide an example of community-based language regulation. In total, 110 discussion threads in which Jodel users make explicit evaluative remarks on others' language use are analyzed. Through an analysis of (de)legitimation strategies, the metalinguistic remarks are explored as key discourse elements in the reproduction of language ideologies. The results show that Jodel users promote and uphold a hypercorrect local ideology that, to a large extent, promotes uniformity and traditional standard orthography. Prominent strategies for invoking this local language ideology are humor, repetition, and exposed correction. The metalinguistic comments are used for the purpose of creating boundaries for inclusion and exclusion of community members on the app.